Reproductive and Production Performance of Andaman Local Pig of Andaman and Nicobar Islands, India under Intensive System of Rearing - Kundu, M. S.; Perumal, P.; Ravi, S. K.; Bhattacharya, D.; Kundu, A.; Sunder, Jai; Muniswamy, K.; Sawhney, Sneha; De, A. K. (International Journal of Bio-resource and Stress Management, 2020)
Andaman local pig (ALP) is available in Andaman and Nicobar Islands (ANI), associated with socio-economic of tribal population. ALP is semi-feral, reared in free-range system with low management. However, population of ALP has reduced significantly due to Tsunami in 2004. No systematic study was conducted to explore the potential of ALP. Therefore, a systematic study was conducted on growth and reproductive parameters. Reproductive parameters like litter size, total and individual litter weight at birth, litter size, total and individual litter weight at weaning and pre and post-weaning mortality were recorded. Growth parameters like body weights from month 1 to 9 were recorded. Besides these, dressing percentage, meat: bone ratio, fat thickness and percentage of lean, fat and bone were recorded. Results revealed that significantly (p≤0.05) higher body weights were observed from month 1 to 9 in male than female. Similarly, significantly higher values in reproductive parameters were observed in male than female. Carcass characters like dressing percentage, meat: bone ratio and fat thickness did not differ significantly between genders whereas percentage of lean, fat and bone differed significantly between them. Fat percentage in female and percentage of lean and bone in male were higher significantly than in other sex. It is concluded that growth, reproductive performances and carcass characteristics of ALP reared under intensive system has significantly higher in male than in female and it is baseline information for conservation and propagation of ALP in ANI. ALP breed is well adapted to the intensive system of rearing.